Avenue 1960s : stories of live, laugh and love in Singapore - Koh, Karen Xin Yue (2014)
This paper presents the Avenue 1960s campaign, an inaugural heritage communication campaign in Singapore that is targeted at the younger generation. Organised by four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University, the campaign hopes to reconnect Singaporean youths with Singapore's heritage, focusing on the nation-building years.